(Re)considering what we know : learning thresholds in writing, composition, rhetoric, and literacy - Adler-Kassner, Linda; Wardle, Elizabeth (Elizabeth Ann) (Utah State University Press, 2019)
"Continues a discipline-wide discussion about identifying key concepts and ideas of writing studies and the relevance of doing so within and beyond the discipline by considering threshold concepts as a framework, considering naming concepts, and new concepts, as well as discussing ways that existing concepts have been used"--